If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + 5 + n = -19 Reorder the terms: 5 + 2n + n = -19 Combine like terms: 2n + n = 3n 5 + 3n = -19 Solving 5 + 3n = -19 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3n = -19 + -5 Combine like terms: 5 + -5 = 0 0 + 3n = -19 + -5 3n = -19 + -5 Combine like terms: -19 + -5 = -24 3n = -24 Divide each side by '3'. n = -8 Simplifying n = -8
| 80/45 | | 7y+10=9y | | 500/18 | | 3(2x-1)=9x+36 | | 3x-2y+4y=1q | | 6(-4-2g)=-7(g-3) | | .5x+5=.75x-4 | | 4(4-4k)=-10-16x | | 6(1-2m)+7m=10 | | z^5/z^-5 | | 4(x-1)=5x-(x+2) | | 2m+3s=m+5s | | 3(a-2)=1a+10 | | t(n)=24-5(n) | | 9-(1-3y)=4+y-3(3-y) | | 21z^7-15z^5/3z^3 | | 6x+5=3x-3 | | 3(2y-7)=5y+17+y | | 16-4m=6(-3+5m) | | 12x+11y=660 | | 8x+18y=41 | | 50000=-218500+X-0.01X | | -2(7r+2)+4=-16-6r | | x+3y=1000 | | 2x^3-5x^2-7=0 | | x(x)=7x | | n+2n+(n-5)=15 | | 6+(a-6)=10 | | -(x+2)+(2x-1)=-(x-1)+2(x-1) | | -36+8t=4(-7+1t) | | 12z-3z+9z= | | 24=3(e-5) |